Transition from endemic behavior to eradication of malaria due to combined drug therapies: An agent-model approach. (7th January 2020) - Sequeira, João; Louçã, Jorge; Mendes, António M.; Lind, Pedro G.
Highlights: Agent-based model of malaria spreading, validated with empirical data for the transmission aspects of this phenomenon. Uncover of a phase transition from prevalence to eradication, by small variations of drug therapies actions. Derivation of critical values of the parameters characterizing the effect of each drug therapy. Emphasis on gametocytemia reduction and on the selective mosquito mortality during parasite development in the mosquito. Quantitative evidence of what is empirically known concerning combined therapies. Abstract: We introduce an agent-based model describing a susceptible-infectious-susceptible (SIS) system of humans and mosquitoes to predict malaria epidemiological scenarios in realistic biological conditions. Emphasis is given to the transition from endemic behavior to eradication of malaria transmission induced by combined drug therapies acting on both the gametocytemia reduction and on the selective mosquito mortality during parasite development in the mosquito. Our mathematical framework enables to uncover the critical values of the parameters characterizing the effect of each drug therapy. Moreover, our results provide quantitative evidence of what was up to now only partially assumed with empirical support: interventions combining gametocytemia reduction through the use of gametocidal drugs, with the selective action of ivermectin during parasite development in the mosquito, may actively promote disease eradication in the long run. In the agent model, the main properties of human-mosquito interactions are implemented as parameters and the model is validated by comparing simulations with real data of malaria incidence collected in the endemic malaria region of Chimoio in Mozambique. Finally, we discuss our findings in light of current drug administration strategies for malaria prevention, which may interfere with human-to-mosquito transmission process.